2012
DOI: 10.1073/pnas.1116800109
|View full text |Cite
|
Sign up to set email alerts
|

H 2 O 2 activates G protein, α 12 to disrupt the junctional complex and enhance ischemia reperfusion injury

Abstract: The epithelial cell tight junction separates apical and basolateral domains and is essential for barrier function. Disruption of the tight junction is a hallmark of epithelial cell damage and can lead to end organ damage including renal failure. Herein, we identify Gα12 activation by H 2 O 2 leading to tight junction disruption and demonstrate a critical role for Gα12 activation during bilateral renal ischemia/reperfusion injury. Madin–Darby canine kidney (MDCK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 40 publications
(46 reference statements)
5
59
0
1
Order By: Relevance
“…4E). Although both H 2 O 2 and PV inhibited phagocytosis, it remained possible that this effect was independent of its effect on KIM-1 shedding (27,74,83,84). We demonstrate that the inhibitory effect of both H 2 O 2 and PV on efferocytosis was rescued by blocking KIM-1 shedding with TAPI-0 pretreatment of cells (Fig.…”
Section: -P Cellsmentioning
confidence: 55%
“…4E). Although both H 2 O 2 and PV inhibited phagocytosis, it remained possible that this effect was independent of its effect on KIM-1 shedding (27,74,83,84). We demonstrate that the inhibitory effect of both H 2 O 2 and PV on efferocytosis was rescued by blocking KIM-1 shedding with TAPI-0 pretreatment of cells (Fig.…”
Section: -P Cellsmentioning
confidence: 55%
“…More recently, the importance of Ga subunits in the recovery of the kidney after ischemic injury was documented in a study by Yu et al (2012). In their report, constitutively active QLa12 mutant transgenic mice were observed to have attenuated recovery after renal IRI with more severe tubular injury compared with the wild-type Ga12 mice.…”
Section: Role Of Gbg In Acute Kidney Injurymentioning
confidence: 93%
“…Prior studies have demonstrated activation of Ga in models of AKI. For example, pharmacologic agonists of the adenosine A2A GPCR (Yap and Lee, 2012) or genetic modulation of Ga12 subunit function (Yu et al, 2012) have been shown to alter the severity of AKI in animal models. However, these studies primarily focused on signaling via Ga subunits through biased signaling cascades activated by upstream GPCRs.…”
Section: Introductionmentioning
confidence: 99%
“…They found a ~1.75-fold increase in RhoA-GTP levels that peaked approximately 5 min post stimulation. 137 Likewise, in the human lung adenocarcinoma epithelial cell line A549, H 2 O 2 was shown to activate RhoA by ~2.5-fold after 15 min, which was concomitant with stress fiber formation. 138 As the mechanism of RhoA activation was not investigated in any of these studies, it is unclear whether RhoA activity is regulated directly by oxidants or indirectly through the redox-sensitive LMW-PTP, another GAP, GEF, or GDI.…”
Section: Redox Regulation Of Rhoamentioning
confidence: 99%